Characterization of Polyhydroxybutyrate, PHB, Synthesized by Newly Isolated Haloarchaea Halolamina spp. - Nashwa Hagagy; Amna A. Saddiq; Hend M. Tag; Samy Selim; Hamada AbdElgawad; Rosa María Martínez-Espinosa (Molecules, 2022)
This work aims to characterize the haloarchaeal diversity of unexplored environmental salty samples from a hypersaline environment on the southern coast of Jeddah, Saudi Arabia, looking for new isolates able to produce polyhydroxyalkanoates (PHAs). Thus, the list of PHA producers has been extended by describing two species of Halolamina; Halolamina sediminis sp. strain NRS_35 and unclassified Halolamina sp. strain NRS_38. The growth and PHA-production were investigated in the presence of different carbon sources, (glucose, sucrose, starch, carboxymethyl cellulose (CMC), and glycerol), pH values, (5–9), temperature ranges (4–65 °C), and NaCl concentrations (100–350 g L−1). Fourier-transform infra-red analysis (FT-IR) and Liquid chromatography–mass spectrometry (LC-MS) were used for qualitative identification of the biopolymer. The highest yield of PHB was 33.4% and 27.29% by NRS_35 and NRS_38, respectively, using starch as a carbon source at 37 °C, pH 7, and 25% NaCl (w/v). The FT-IR pattern indicated sharp peaks formed around 1628.98 and 1629.28 cm−1, which confirmed the presence of the carbonyl group (C=O) on amides and related to proteins, which is typical of PHB. LC-MS/MS analysis displayed peaks at retention times of 5.2, 7.3, and 8.1. This peak range indicates the occurrence of PHB and its synthetic products: Acetoacetyl-CoA and PHB synthase (PhaC). In summary, the two newly isolated Halolamina species showed a high capacity to produce PHB using different sources of carbon. Further research using other low-cost feedstocks is needed to improve both the quality and quantity of PHB production. With these results, the use of haloarchaea as cell factories to produce PHAs is reinforced, and light is shed on the global concern about replacing plastics with biodegradable polymers.